(untitled) (Journal of Business Management and Accounting, 2015)
The Malaysian timber industry is a competitive industry that has the potential to grow. Since most of the production in this industry is for the export market, the global economic conditions and competition from other producing countries will nevertheless affect the performance of the industry. Therefore, in order for this market to expand, the quality of timber production should be further enhanced and offered at a more competitive price. Generally, issues related to high dependency on foreign workers and low level of automation are believed to seriously affect the viability and sustainability of the Malaysian timber industry. Following these issues, a case study was carried out on Besgrade Products Sdn. Bhd., which is one of the largest plywood manufacturers in Malaysia. The findings revealed that, in general, the percentage of foreign workers in the company is far higher than the percentage of local workers. It was also found that the majority of foreign workers occupied the operator position. Probing further into the problem facing by the firm in hiring local workers revealed that long working hours and unpleasant work environment are the major factors that contribute toward low participation of local workers. With regard to foreign workers, communication problems and â€œred tapeâ€ in permit approval are among the major issues. Based on the findings, various suggestions related to labour issues have been put forth. These include the rebranding of the timber industry to be more dynamic, providing a more conducive work environment, introducing competitive wages for local workers, intensifying efforts toward automation through the use of technology thereby promoting the training of skilled workers who can handle high technology machines, and finally establishing policies to gradually reduce the dependency on foreign labour while at the same time training local workers with the necessary skills.